Evaluación agronómica de cinco variedades de lechuga (Lactuca sativa L.) en tres ciclos de siembra consecutivos en San Miguel de la Tigra, San Carlos, Alajuela, C. R. - Vásquez-Camacho, Jason G. (Instituto Tecnológico de Costa Rica, 2015)
Due to that the area of San Carlos is highly touristic and therefore demandant of horticultural products, among them the lettuce. In the absence of knowledge about varieties that will produce in open field under the prevailing conditions of the area, it was decided to evaluate agronomically 5 varieties of iceberg lettuce in 3 consecutive cycles of planting. The field evaluation was conducted on three different dates for each cycle: the first cycle comprised of June 19 to July 29 2014, the second cycle comprised of August 03 to September 23 2014 and the third cycle comprised from October 02 to November 13 2014. In each of these cycles 5 varieties of American lettuce; (Lucy Brown, Vulcan, Bergam’S Green, Sargasso and Bohemia) were used. With these two factors, the research was a completely randomized design, with factorial arrangement 5 x 3 and 4 repetitions each. Weather conditions for the characterization of each cycle, growth variables and quality of lettuce varieties were measured. Using nonparametric (Kruskal Wallis) and parametric statistics (ANOVA and Tukey test = 0.05) found than the best performance in both growth and quality, occurred in cycle 2. Despite having the highest temperature and luminous intensity, this cycle presented lower relative humidity and lower rainfall. The varieties best behaved as assessed were Lucy Brown and Sargasso, however in no event came to have a suitable growth for marketing.
Proyecto de graduación (Licenciatura en Ingeniería en Agronomía) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Agronomía, 2015
Keywords: Lechuga; Evaluación agronómica; Calidad